12 - Indigenous African Knowledge and the Challenge of Epistemic Translation - Zubairu Wai (CODESRIA Bulletin, 2025)
Keynote Address: African Fellowships for Research in Indigenous and Alternative Knowledges (AFRIAK), Conference organised by CODESRIA, King Fahd Palace Hotel – Dakar, Senegal, 25–27 November 2024 Prologue Allow me to start by recalling an encounter at another CODESRIA meeting in Dakar, in January 2013. In collaboration with Point Sud (Centre for Research on Local Knowledge), based in Bamako, Mali, CODESRIA had co-organised a conference, ‘Africa N‘ko: Debating the Colonial Library’. The conference had brought together some of Afri- ca’s ﬁnest intellectuals to consider the implications of what Congolese philosopher V.Y. Mudimbe designated a ‘colonial library’ on knowledge production and gnostic practices on and about Africa, as well as imagine the continent beyond the epistemic regions, structuring violence and contaminating vectors of this library. Coinciding with the conference was Operation Serval, a French military intervention in Mali os- tensibly to oust Al-Qaeda-linked Islamists who had seized control of the north of Mali and were pushing into the centre of the country. Like every other ‘savage war for peace’, Operation Serval was justiﬁed in the name of a higher ethical purpose: namely, to prevent the Mali- an state from collapse and rescue it from the savagery of Islamists harkening to irrational and premodern beliefs. Among those attending the conference, however, the concerns were especially over the protection of historical and cultural artefacts – speciﬁcally, the manuscripts and knowledge troves of medieval West Africa housed in a library in Timbuktu, central Mali.